EXPLORING SECONDARY STUDENTS’ PERCEPTION AND PRACTICE ON DIALOGIC READING STRATEGY IN READING COMPREHENSION - Hersagita Anissa Hayati; Dayat Hidayat; Muhammad Reza Pahlevi (PROJECT (Professional Journal of English Education), 2022)
This study aimed to found out students’ perception and practice in using dialogic reading strategy. This research used qualitative method and case study approach. The participant took from three secondary school students in Karawang. The data of this research collected through observation, interview, and documentation. The result of this study found out that dialogic reading strategy can engage student in reading comprehension such as dialogic reading makes students more understand about context of the text, it increase students vocabulary, and it make students more active and confident in learning English. Keywords:  Dialogic Reading, Reading Comprehension, Student Perception